Suboptimal Midcourse Guidance with Terminal-Angle Constraint for Hypersonic Target Interception - Shizheng Wan; Xiaofei Chang; Quancheng Li; Jie Yan (International Journal of Aerospace Engineering)
For the problem of hypersonic target interception, a novel midcourse guidance method with terminal-angle constraint is proposed. Referring to the air-breathing and the boost-gliding hypersonic targets, flight characteristics and difficulties of interception are analyzed, respectively. The requirements of midcourse guidance for interceptors are provided additionally. The kinematics model of adversaries is established concerning line-of-sight coupling in longitudinal and lateral planes. Suboptimal guidance law with terminal-angle constraint, specifically the final line-of-sight angle or impact angle, is presented by means of model predictive static programming. The trajectory is optimized and the load factor would finally converge after penalizing control sequence and output deviations. The realization of terminal angle is firstly verified with a constant speed target. A full interception scenario is further simulated focusing on a typical boost-gliding target, which flies along a skipping trajectory. Results show the success of providing handover conditions for intercepting hypersonic targets.